ANALISIS KEMITRAAN BERBASIS PENTAHELIX DALAM KOMUNIKASI PUBLIK PADA FORUM PENDAMPINGAN, KOMUNIKASI DAN KEMITRAAN PELAYANAN PUBLIK BLUD RUMAH SAKIT KONAWE - Arifin Utha; Zulfiah Larisu; La Ode Mustafa R; Irman; La Ode Aslim (Halu Oleo University, 2024)
The purpose of this study is to describe and analyze the implementation of Pentahelix-based partnership in public communication at the BLUD Konawe Hospital Public Service Assistance, Communication and Partnership Forum, and to analyze the Supporting and Inhibiting Factors of Pentahelix-Based Partnership performance in Public Communication at the BLUD Konawe Hospital Public Service Assistance, Communication and Partnership Forum. In this study, the method used is a descriptive qualitative approach. The informants in this study were government officials, academics, private sector (businessmen), media and communities, who have the capability of understanding and credibility related to this study, who are members of the BLUD Konawe Hospital Public Service Assistance, Communication and Partnership Forum. The data analysis used is qualitative. The results of the study indicate that the BLUD Konawe Hospital Public Service Assistance, Communication and Partnership Forum has been running effectively so far, but not optimally. In its implementation, stakeholders in carrying out their duties and functions are still felt to be less than optimal in certain areas. In the performance of this forum, some factors have an influence, both as obstacles and supporters, which will be measured based on indicators, namely: Productivity, Service Quality, Responsiveness, Responsibility and Accountability.